Cryopreservation Induces Alterations of miRNA and mRNA Fragment Profiles of Bull Sperm - Shangguan, Aishao; Zhou, Hao; Sun, Wei; Ding, Rui; Li, Xihe; Liu, Jiajia; Zhou, Yang; Chen, Xing; Ding, Fengling; Yang, Liguo; Zhang, Shujun (Frontiers in Genetics, 2020)
Although cryopreservation of bull semen is widely used commercially in the livestock breeding industry, cryopreservation results in low fertility of bull sperm. As an important regulatory factor, the alteration of small noncoding RNA (sncRNA) profile during cryopreservation of bull sperm is not yet completely known. In the present study, we sequenced sncRNAs of frozen and fresh sperm to study the link of alteration of the sncRNA profiles (particularly in miRNAs and mRNA fragments) with low sperm fertility caused by cryopreservation. We identified 55 miRNAs and 526 mRNA fragments differentially expressed (DE) between frozen and fresh sperm. Subsequently, the functional analysis revealed that targeted genes of DE miRNAs in sperm had roles in the fertilization, ATP, and apoptosis. Instead, targeted genes of DE miRNAs in bull metaphase II oocyte were significantly enriched in the MAPK signaling pathway, autophagy-animal pathway, and mitophagy-animal pathway. Additionally, biological processes of DNA repair, spermatid development, response to temperature stimulus, and cellular response to DNA damage stimulus were enriched by mRNA fragments. In conclusion, we found that DE miRNAs or DE mRNA fragments in cryopreservation may influence the fertility of sperm, these findings will provide the reference to improve the cryopreservation technology of bull semen.